Competition Model and the Change of Local Governments' Behavior—and Governance of China's Local Government Debt. Issue 3 (3rd May 2016) - Li, Shujuan; Liang, Yan
Abstract : "Promotion tournament model" is used to explain the Chinese economic miracle. The key of the promotion tournament model is competition for economic growth which brings economic growth together with some societal problems. Competition for economic growth influences local governments' behavior and is one of the reasons for the rapid rising of local debts. The article proposes a new competition model—competition for inhabitants' satisfaction. It is a better choice under the system of political centralization with fiscal decentralization in China. It gives inhabitants the right to supervise the government officials while the central government has the power of appointment. Competition for inhabitants' satisfaction changes the local governments' investment and finance behaviors, which is meaningful to improve China's local government debt governance.